2017
DOI: 10.1515/jbcpp-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging effects of M2000 (β-D-mannuronic acid) as a novel immunosuppressive drug on the enzymatic and non-enzymatic oxidative stress parameters in an experimental model

Abstract: Our data showed the anti-aging property of M2000 as a novel designed non-steroidal anti-inflammatory drug (NSAID) with immunosuppressive property on various oxidative stress determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…β-D-mannuronic acid (M2000) and its analog α-l-guluronic acid (G2013) are novel non-steroidal anti-inflammatory drugs (NSAIDs) currently being studied. In relation to oxidative stress, M2000 and G2013 non-significantly increase regulatory enzymes related to oxidative stress, but investigation of these two NSAIDs should not be immediately abandoned (Afraei et al, 2015 ; Mirshafiey et al, 2016 ; Hosseini et al, 2017 ). The mode of action for M2000 has been postulated as both a TLR2/TLR4 antagonist (Aletaha et al, 2017 ) and a miR-155 inhibitor (Pourgholi et al, 2017 ).…”
Section: Inhibiting the Inflammatory Pathwaymentioning
confidence: 99%
“…β-D-mannuronic acid (M2000) and its analog α-l-guluronic acid (G2013) are novel non-steroidal anti-inflammatory drugs (NSAIDs) currently being studied. In relation to oxidative stress, M2000 and G2013 non-significantly increase regulatory enzymes related to oxidative stress, but investigation of these two NSAIDs should not be immediately abandoned (Afraei et al, 2015 ; Mirshafiey et al, 2016 ; Hosseini et al, 2017 ). The mode of action for M2000 has been postulated as both a TLR2/TLR4 antagonist (Aletaha et al, 2017 ) and a miR-155 inhibitor (Pourgholi et al, 2017 ).…”
Section: Inhibiting the Inflammatory Pathwaymentioning
confidence: 99%
“…According to the previous studies, the immunosuppressive effects of M2000 were found in animal models and cell lines [21-24, 90]; Also, anti-oxidant property of M2000 and its monomer, G2013 has been proven in animal models [25, 32]. Recently, the results of a clinical trial showed that M2000 has an inhibitory effect on Anti-Cyclic Citrullinated Peptide Antibodies (anti-CCP), Rheumatoid Factor (RF), anti-double strand DNA (anti-dsDNA) and acute phase reactants in RA patients [91].…”
Section: Discussionmentioning
confidence: 99%
“…We know that oxidative stress damages the mucosal layer of intestines, leading to bacterial invasion, and IBD development [6]. Therefore, due to the capacity of M2000 in suppressing TLR2 and TLR4 and its role in oxidative stress reduction M2000 [25, 32] we anticipate a potent capacity of M2000 for preventing IBD. More comprehensive in vitro and in vivo studies are needed to recognize the molecular mechanism of M2000 and also its probable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations